Use of Electrokinetics in the Remediation of Low Permeability Soils - Reynolds, David; Wu, Ming Zhi; Hodges, Danie; Fourie, Andy; Thomas, David (Águas Subterrâneas, 2011)
A promising method for remediation of low-permeability aquifers is the electrokinetic transport of amendments for in-situ chemical oxidation. Laboratory results have shown the approach to be capable of migrating chemicals through low permeability clays at rates orders of magnitude greater than hydraulic advection or diffusion. Stalling or rapid dispersion of the treatment fluid fronts, however, was observed in most experiments. Stalling is attributed to the influence of low pH due to the migration of H+ generated through electrolysis at the anode. Numerical modelling showed that amendment injection resulted in the voltage gradient adjacent to the cathode decreasing below a linear gradient resulting in a higher voltage gradient with distance from the injection point, and therefore lower achievable concentrations of the amendment in the medium. Even with low achievable concentrations, analysis showed that electrokinetic remediation is feasible due to its ability to deliver a significantly higher mass flux in low permeability media than under a hydraulic gradient.